Texas amphibians : a field guide - Tipton, Bob L., 1948- (Texas natural history guides., 2012)
With a wide variety of habitats ranging from southeastern swamps to western deserts, Texas is home to numerous species of frogs, toads, and salamanders. Each area of Texas has a particular set of species that has evolved there over thousands of years. Indeed, most amphibians are not very mobile, and many live their entire lives within a few square meters. This makes them particularly vulnerable to environmental degradation and habitat destruction. Texas Amphibians is the only field guide focused exclusively on the state?s frogs, toads, and salamanders. It presents brief, general accounts of the two orders and fifteen families. Then it identifies each of the seventy-two species in detail, including size, description, voice (if applicable), similar species, distribution (with maps), natural history, reproduction, subspecies (if applicable), and comments and conservation information. Color photographs illustrate the species. The book also includes a general introduction to amphibian natural history, conservation, observation and collection, maintenance in captivity, museum and preserved specimens, and scientific and common names, as well as scientific keys to Texas salamanders and frogs and a generic key to amphibian larvae. This wealth of information, compiled by a team of experts who collectively have over a century of experience in field herpetology, will increase our appreciation for amphibians and the vital role they play as an early indicator of threats to the quality of the environment that we all share.